2007
DOI: 10.1002/jbm.a.31382
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin silanized titanium alloy: A bioinductive and durable coating to enhance fibroblast attachment in vitro

Abstract: Long term success of percutaneous implants is dependent on soft tissue attachment to prevent infection and epithelial downgrowth, which leads to failure of the implant. Fibronectin coatings are known to enhance fibroblast attachment in vitro, but are subject to desorption from serum protein competition in vivo. This paper quantifies the binding of fibronectin to titanium alloy by silanization and the durability of this attachment when soaked in protein-rich fluid compared with adsorbed fibronectin. The biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
89
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(95 citation statements)
references
References 25 publications
4
89
1
Order By: Relevance
“…Functional silanes, such as γ-APS, have often been used for modification of stainless steel [33] and Ti [30,34] to provide surface functionality for post chemical anchorage of biomolecules (e.g. collagen, heparin and fibronectin), with a view to improving the biocompatibility of these metallic implants.…”
Section: Corrosion Resistance Properties Of the Modified Az31 Mg Alloysmentioning
confidence: 99%
“…Functional silanes, such as γ-APS, have often been used for modification of stainless steel [33] and Ti [30,34] to provide surface functionality for post chemical anchorage of biomolecules (e.g. collagen, heparin and fibronectin), with a view to improving the biocompatibility of these metallic implants.…”
Section: Corrosion Resistance Properties Of the Modified Az31 Mg Alloysmentioning
confidence: 99%
“…Previous studies have indicated that silane treatment on various substrate surfaces, such as gold, platinum, Ti, and glass, can promote cell adhesion and proliferation [11] and enhance the adhesive ability of cells [9]. Silanization involves binding silane to substrate surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium (Ti) surfaces are coated with a stable and bioinert titania oxide layer, and thus, researchers have used silane as the grafting bridge between Ti substrates and proteins through varied sequences to install various amino acids in a polypeptide chain to this type of surface [9][10][11]. Previous studies have indicated that silane treatment on various substrate surfaces, such as gold, platinum, Ti, and glass, can promote cell adhesion and proliferation [11] and enhance the adhesive ability of cells [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,4 Fibronectin is a glycoprotein that contains an arginine-glycine-aspartate (RGD) amino acid sequence that attaches cells via integrins and increases fibroblast adhesion. 18 Fibronectin may be adsorbed onto hydroxyapatite to further enhance the effects of hydroxyapatite on soft tissue attachment. 3,19,20 For example, Pendegrass et al implanted subcutaneous plates into sheep tibia and found that fibronectin-functionalized hydroxyapatite (HAFn) coatings were associated with greater dermal tissue ingrowth and attachment than nonfunctionalized hydroxyapatite coatings.…”
Section: Introductionmentioning
confidence: 99%